2020
DOI: 10.1002/bies.202000215
|View full text |Cite
|
Sign up to set email alerts
|

Epidural fat mesenchymal stem cells: Important microenvironmental regulators in health, disease, and regeneration

Abstract: Mesenchymal stem cells (MSCs) are present in fat tissues throughout the body, yet little is known regarding their biological role within epidural fat. We hypothesize that debridement of epidural fat and/or subsequent loss of MSCs within this tissue, disrupts homeostasis in the vertebral environment resulting in increased inflammation, fibrosis, and decreased neovascularization leading to poorer functional outcomes post‐injury/operatively. Clinically, epidural fat is commonly considered a space‐filling tissue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…However, several difficulties have been observed in conducting basic studies with EF-MSCs. To date, EVs have been considered as novel source materials for regenerative studies and clinical relevance [3,[7][8][9]29]. EVs exhibit several advantages for such research, and one of their advantages over MSCs is that they do not consume their donor tissues or cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several difficulties have been observed in conducting basic studies with EF-MSCs. To date, EVs have been considered as novel source materials for regenerative studies and clinical relevance [3,[7][8][9]29]. EVs exhibit several advantages for such research, and one of their advantages over MSCs is that they do not consume their donor tissues or cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a basic study has indicated that EF contains mesenchymal stem cells (MSCs) [ 1 , 2 ]. A few studies have shown that MSCs derived from EF can produce an affirmative effect for specific pathologies in the spine, such as spinal cord injury and post-lumbar surgery syndrome [ 2 , 3 ]. However, spine physicians are ill-informed on EF.…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 ] Therefore, it is not uncommon for this tissue to be discarded during surgical procedures. [ 28 ] However, there is a growing body of evidence suggesting that epidural fat is necessary to maintain the dural microenvironment and that the absence of epidural fat can lead to worse post‐operative outcomes. [ 41 ] Recognizing its importance, studies using adipose‐derived MPCs within scaffolds and matrices have attempted to reconstruct epidural fat and have showed reduced adherence of fibrotic tissue to the dura mater when used in injury models.…”
Section: Discussionmentioning
confidence: 99%
“…We have also used this mouse to determine that MPCs in the epidural fat and dura express Prx1. [13,15,28,29] We further employed this lineage tracking method on a p21 −/− background to identify if there was a change in behavior of these MPCs in vivo with the deletion of p21.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the need for research on the characteristics and functions of epidural fat tissue has emerged. Studies have reported that MSCs can also be isolated from epidural fat tissue, and that the isolated MSCs exhibited therapeutic effects [11,16,21,40,41]. However, the specific characteristics and functions of human epidural fat MSCs and human epidural fat MSC-derived EVs are not yet clear.…”
Section: Discussionmentioning
confidence: 99%